The treatment of intertrochanteric fracture: a survey on the preferred treatment used by orthopedic surgeons in Campania - Pezzella, Raffaele; Toro, Giuseppe; Errico, Giacomo; Pellegrino, Achille; Medici, Antonio; Bruno, Gaetano; A.C.O.T.O members, on behalf the (Lo Scalpello - Journal, 2021)
Hip fragility fractures incidence is constantly increasing, and outcomes are mostly poor in terms of both morbidity and mortality. Surgery is the treatment of choice for most hip fractures, but the choice between the various fixation devices is difficult. We conducted a survey on the treatment of trochanteric fractures among orthopedic surgeons in Campania using a Google form questionnaire. The preferred treatment was cephalomedullary distal locked nailing for most fractures, while sliding hip screws and hip replacement were limited to 31 A1.2 and 31.B2 fractures.